Molecular Aspects of Plant Beneficial Microbes in Agriculture 2020
DOI: 10.1016/b978-0-12-818469-1.00014-6
|View full text |Cite
|
Sign up to set email alerts
|

Knock, knock-let the bacteria in: enzymatic potential of plant associated bacteria

Abstract: Chapter outline 13.1 Introduction 169 13.2 Amylases 170 13.3 Cellulases, pectinases and xylanases 171 13.4 Chitinases 172 13.5 Lectins 173 13.6 Lipases 174 13.7 Proteases 174 13.8 Conclusions and future perspectives 175 References 175 169 Molecular Aspects of Plant Beneficial Microbes in Agriculture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 89 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…These bacterial isolates also show positive results for the production of cell wall-degrading enzymes such as cellulase, chitinase, and HCN that can hydrolyze fungal cell wall components consisting of proteins and chitin, β-1,3-glucanase; it has been shown to mediate positive response in the biocontrol of fungal pathogens [80]. Cellulase produced by beneficial bacteria plays a very important role in bacterial penetration inside the plant and helps in plant colonization [81]. The results of the present study provided encouraging results regarding the application of plant growth-promoting antagonistic endophytic bacteria with the drought-tolerant potential isolated from soybean roots.…”
Section: Discussionmentioning
confidence: 99%
“…These bacterial isolates also show positive results for the production of cell wall-degrading enzymes such as cellulase, chitinase, and HCN that can hydrolyze fungal cell wall components consisting of proteins and chitin, β-1,3-glucanase; it has been shown to mediate positive response in the biocontrol of fungal pathogens [80]. Cellulase produced by beneficial bacteria plays a very important role in bacterial penetration inside the plant and helps in plant colonization [81]. The results of the present study provided encouraging results regarding the application of plant growth-promoting antagonistic endophytic bacteria with the drought-tolerant potential isolated from soybean roots.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrolytic and carbohydrate-binding enzymes, such as cellulases, xylanases, pectinases, chitinases, amylases, proteases, and lectins, play a vital role in biocontrol against pathogens. They are essential in colonizing plant surfaces and inducing plant resistance (Carro and Menéndez 2020;Chernin and Chet 2002). The Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the tested bacterial strains exhibited a wide spectrum of hydrolytic enzymes with potential in plant protection and growth promotion. In some cases, α-amylase production by plant growth-promoting bacteria is a beneficial trait, as it can be correlated with gibberellin phytohormone synthesis [82]. In plants other than grapevine, bacterial α-amylase release is also relevant in stimulating the seed germination process, triggering improved seedlings' root and shoot growth [83].…”
Section: Discussionmentioning
confidence: 99%